Simulation for analysis of the echo by a multifrequency radio wave sounder (abstract) - Izumi, Tatsushi; Hoshiyama, Mitsuo; Nishitsuji, Akira; Wada, Makoto; Mae, Shinji; Kusunoki, Kou (1984)
P(論文) departmental bulletin paper